Ground cover rice production systems increase soil carbon and nitrogen stocks at regional scale - Liu, M.; Dannenmann, Michael; Lin, S.; Saiz, G.; Yan, G.; Yao, Z.; Pelster, David E.; Tao, H.; Sippel, S.; Tao, Y.; Zhang, Y.; Zheng, X.; et al. (Copernicus GmbH, 2015)
Abstract. Rice production is increasingly limited by water scarcity. Covering paddy rice soils with films (so-called ground cover rice production system: GCRPS) can significantly reduce water demand as well as overcome temperature limitations at the beginning of the growing season, which results in greater grain yields in relatively cold regions and also in those suffering from seasonal water shortages. However, it has been speculated that both increased soil aeration and temperature under GCRPS result in lower soil organic carbon and nitrogen stocks. Here we report on a regional-scale experiment conducted in Shiyan, a typical rice-producing mountainous area of China. We sampled paired adjacent paddy and GCRPS fields at 49 representative sites. Measured parameters included soil carbon (C) and nitrogen (N) stocks (to 1 m depth), soil physical and chemical properties, δ15N composition of plants and soils, potential C mineralization rates, and soil organic carbon (SOC) fractions at all sampling sites. Root biomass was also quantified at one intensively monitored site. The study showed that: (1) GCRPS increased SOC and N stocks 5–20 years following conversion from traditional paddy systems; (2) there were no differences between GCRPS and paddy systems in soil physical and chemical properties for the various soil depths, with the exception of soil bulk density; (3) GCRPS increased above-ground and root biomass in all soil layers down to a 40 cm depth; (4) δ15N values were lower in soils and plant leaves indicating lower NH3 volatilization losses from GCRPS than in paddy systems; and (5) GCRPS had lower C mineralization potential than that observed in paddy systems over a 200-day incubation period. Our results suggest that GCRPS is an innovative production technique that not only increases rice yields using less irrigation water, but that it also increases SOC and N stocks.